Mechanical properties of woven banana fibre reinforced epoxy composites - Salit, Mohd Sapuan; A., Leenie; Mohamed, Harimi; Yeo, Kay Beng (Elsevier, 2006)
In this paper, the experiments of tensile and flexural (three-point bending) tests were carried out using natural fibre with composite materials (Musaceae/epoxy). Three samples prepared from woven banana fibre composites of different geometries were used in this research. From the results obtained, it was found that the maximum value of stress in x-direction is 14.14 MN/m2, meanwhile the maximum value of stress in y-direction is 3.398 MN/m2. For the Young’s modulus, the value of 0.976 GN/m2 in x-direction and 0.863 GN/m2 in y-direction were computed. As for the case of three-point bending (flexural), the maximum load applied is 36.25 N to get the deflection of woven banana fibre specimen beam of 0.5 mm. The maximum stress and Young’s modulus in x-direction was recorded to be 26.181 MN/m2 and 2.685 GN/m2, respectively. Statistical analysis using ANOVA-one way has showed that the differences of results obtained from those three samples are not significant, which confirm a very stable mechanical behaviour of the composites under different tests. This shows the importance of this product and allows many researchers to develop an adequate system for producing a good quality of woven banana fibre composite which maybe used for household utilities.